PERANCANGAN JIG SEBAGAI ALAT BANTU PADA PROSES TINNING DI PT XYZ - Firdaus, Hamdi; Ganda Sirait (LPPM Universitas Putera Batam, 2024)
The high demand for manufactured products has grown rapidly, therefore, to be able to meet the demand for manufactured products, producers must think of ways to always be innovative so that quality products can be produced quickly. Design is an activity of defining things that are done using a variety of technical knowledge. PT XYZ, where in the lighting department the tinning process is carried out on the bobbin pin material for trigger coil products. The tinning process was carried out manually without tools. Problems occurred when the pin tinning process was carried out manually one by one by the operator with an average time of 7.82 seconds/piece, making the production target not achieved due to an increase in demand. By using the Design For Manufacturing and Assembly method for jig design. Based on DFMA analysis, the fabrication cost was IDR 537,580 and the fabrication time was 3.56 hours. The successful implementation of the jig reduced the tinning process per day, because the tinning process using the jig could be done directly in 10 pieces, previously 2,240 processes became 1,129 processes per day. In terms of output, the shift also increased, previously from 2,240 pieces to 11,290 pieces.